Lysosomal Enzyme Activities in Platelets of Normal Individuals and of Patients with Gaucher’s Disease - Yatziv, S; White, M; Eldor, A (Thrombosis and Haemostasis, 1974)
Five platelet lysosomal enzyme activities were estimated in 22 normal individuals and in 5 patients with Gaucher’s disease: ß-D-galactosidase, N-Acetyl-ß-D-glucosa-minidase, N-Acetyl-ß-D-galactosaminidase acid-phosphatase, and ß-D-glucuronidase.In the 5 patients with Gaucher’s disease the specific activities for the first four of these enzymes were significantly higher than in normal individuals. The activity of acid-phosphatase, on the other hand, was lower in G. d. than in normals. The release of the 5 lysosomal enzymes from platelets upon incubation with thrombin was also examined in the same two groups. The only lysosomal enzyme that was not released from normal platelets was acid-phosphatase. In Gaucher’s patients, on the other hand, acid-phosphatase was invariably released from platelets when incubated with thrombin. The release of the other four enzymes from platelets of Gaucher patients was similar to that of normal controls.